Respiratory Similarity in Monozygotic Twins - Jayakumar T; Savithri S.R (Journal of All India Institute of Speech and Hearing)
Twins are one of the integral members in the society. It is generally accepted that the physical characteristics of the laryngeal mechanisms are genetically determined. Since Lung volume and air flow are the source of voice production; it is vice to investigate the similarity of respiratory parameters (voice source). Slow vital capacity (SVC) and Mean air flow rate (MAFR) was investigated using Spirometer (RMS Helios 501). 17 monozygotic twins (MZ) pairs (11 F and 6 M pairs) with mean age of 22.1 yrs and age and gender matched normal subjects were participated in the study. Pearson with in pair correlation should high positive coefficient value. Only SVC showed gender differences for raw scores. No influence of age and gender on respiratory similarity. But, male showed less similarity than female. Discriminant analysis showed separation of twins group from the normal; separation was greater for absolute differences score. In conclusion present study showed similarity in SVC and MAFR of monozygotic twins. It supports the theory of genetic influence on respiratory functions.